2022
DOI: 10.1002/ajpa.24658
|View full text |Cite
|
Sign up to set email alerts
|

Ecological divergence and calcaneal‐cuboid morphology in gorillas

Abstract: ObjectivesGorillas are diverse behaviorally and ecologically with higher frequencies of arboreality and frugivory observed in populations living at lower altitudes compared to those living at higher altitudes. Previous studies have shown that the more arboreal western lowland gorilla has hallucial tarsometatarsal and talocrural joint morphologies associated with enhanced hallucial abduction and foot inversion capabilities whereas the more terrestrial eastern gorilla does not. Here we examine how known ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 127 publications
(349 reference statements)
0
10
0
Order By: Relevance
“…Calcaneal external morphology is quite variable among extant hominoids and is functionally correlated with known locomotor variation (Harper et al, 2021a, 2021b, 2022; Kidd, 1999; Latimer & Lovejoy, 1989; McNutt & DeSilva, 2020; Nozaki et al, 2021; Prang, 2015, 2016; Prang & Tocheri, 2024). For example, more arboreal non‐human hominoids have a cuboid facet that is relatively larger and has a deeper pivot region, two features that have been suggested to increase mobility at the calcaneocuboid joint during inversion and eversion (Gebo, 1992; Harper et al, 2021a, 2021b; Prang & Tocheri, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcaneal external morphology is quite variable among extant hominoids and is functionally correlated with known locomotor variation (Harper et al, 2021a, 2021b, 2022; Kidd, 1999; Latimer & Lovejoy, 1989; McNutt & DeSilva, 2020; Nozaki et al, 2021; Prang, 2015, 2016; Prang & Tocheri, 2024). For example, more arboreal non‐human hominoids have a cuboid facet that is relatively larger and has a deeper pivot region, two features that have been suggested to increase mobility at the calcaneocuboid joint during inversion and eversion (Gebo, 1992; Harper et al, 2021a, 2021b; Prang & Tocheri, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The hominid calcaneus (Figure 1), in particular, could be a valuable skeletal element to study given its multiple articulations with other bones, its role as a lever for the plantarflexor muscles, and its weight-bearing role during the stance phase of the gait cycle. Moreover, it has already been demonstrated that its external shape is correlated with different locomotor behaviors (e.g., Gebo, 1992;Harper et al, 2021aHarper et al, , 2021bHarper et al, , 2022Kidd, 1999;Latimer & Lovejoy, 1989;Levine et al, 2014;McNutt & DeSilva, 2020;Nozaki et al, 2021;Prang, 2015Prang, , 2016Prang & Tocheri, 2024;Schmitt & Larson, 1995;Zeininger et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several of these papers combine Mary's lifelong pursuits of methods to quantify complex shape variation to improve understanding of the relationship between primate functional morphology and locomotor behavior, spanning the foot, leg, hand, vertebrae, and pelvis. Friesen et al (2024) examine variation in talar and medial cuneiform shape among chimpanzees and bonobos using 3D geometric morphometrics, while Prang and Tocheri (2024) explore variation in gorilla calcaneal‐cuboid morphology in relation to differences in ecology using biomechanically‐informed 3D measurements of the size and orientations of their articular surfaces and the calcaneal tuber. Two articles focus on covariation of morphology within the wrist and hand, also applying 3D geometric morphometrics: (1) Bardo et al (2024) examine the first carpometacarpal joint and (2) Vanhoof et al (2024) investigate distal ulnar and triquetrum shape.…”
mentioning
confidence: 99%